Deafness gene mutations in newborns in Beijing. (3rd May 2016) - Han, Shujing; Yang, Xiaojian; Zhou, Yi; Hao, Jinsheng; Shen, Adong; Xu, Fang; Chu, Ping; Jin, Yaqiong; Lu, Jie; Guo, Yongli; Shi, Jin; Liu, Haihong; et al.
ABSTRACT: Objective To determine the incidence of congenital hearing loss (HL) in newborns by the rate of deafness-related genetic mutations.Design Clinical study of consecutive newborns in Beijing using allele-specific polymerase chain reaction-based universal array.Study sample This study tested 37 573 newborns within 3 days after birth, including nine sites in four genes: GJB2 (35 del G, 176 del 16, 235 del C, 299 del AT), SLC26A4 (IVS7-2 A > G, 2168 A > G), MTRNR1 (1555 A > G, 1494 C > T), and GJB3 (538 C > T). The birth condition of infants was also recorded.Results Of 37 573 newborns, 1810 carried pathogenic mutations, or 4.817%. The carrier rates of GJB2 (35 del G, 176 del 16, 235 del C, 299 del AT), GJB3 (538 C > T), SLC26A4 (IVS7-2 A > G, 2168 A > G), and MTRNR1 (1555 A > G, 1494 C > T) mutations were 0.005%, 0.104%, 1.924%, 0.551%, 0.295%, 0.253%, 1.387%, 0.024%, and 0.274%, respectively. Logistic regression analysis indicated no statistically significant relationship between mutations and infant sex, premature delivery, twin status, or birth weight.Conclusions The 235delC GJB2 mutation was the most frequent deafness-related mutation in the Chinese population. Genetic screening for the deafness gene will help detect more cases of newborn congenital HL than current screening practices.